Taboo Words (Haba Geutham) As A Morals In Language and Psychological Effect in Pidie Community - Vera Wardani Vera; Nuraiza Nuraiza (UNIVERSITAS SERAMBI MEKKAH, 2021)
This study aims to describe taboo words (haba geutham) as a form of language adab and the impact of psychological influences on Pidie community activities. This type of research is field research using a qualitative approach. The method used is descriptive-analytical. The data of this research are taboo words (haba geutham) as a form of language adab and the impact of psychological influences on the activities of the Pidie community. The data source of this research is informants, namely the people who live in Pidie district. The data was collected using structured interview techniques which are supported by inducement techniques. The data analysis technique used is the stage analysis technique, selecting data, describing the entire data, grouping the data, and analyzing the data. The results of the research found were taboo words (haba geutham) as a form of language adab in Pidie community activities including, (1) taboo language of words relating to animals, (2) taboo language regarding spirits (3) taboo language -words relating to disease, (4) taboo language of words relating to farming activities, (5) taboo language of words relating to hunting activities, (6) taboo language of words relating to nighttime, (7) taboo language words relating to the tradition of marriage, (8) taboo language of words relating to body organs, (9) taboo language of words relating to femininity, (10) taboo language of words relating to the genitals and sexual organs, ( 11) taboo language of words relating to sexual activity, and (12) taboo language of words relating to certain words. Regarding the impact of the psychological influence of taboo words (haba geutham) on community activities Pidie has a negative impact because it is caused by speech, (1) taboo words (haba geutham) because of fear, (2) taboo words (haba geutham) ) because they feel uncomfortable or uncomfortable, (3) taboo words (haba geutham) because they feel impolite and impolite, and (4) taboo words (haba geutham) are contrary to religion.